Jezus Chrystus Najwyższy Kapłan w świetle Listów do kapłanów na Wielki Czwartek Jana Pawła II - Bogusław Kochaniewicz (Studia Koszalińsko-Kołobrzeskie, 2023)
This article presents an analysis of John Paul II’s Letters to Priests for Maundy Thursday. Published throughout his pontificate, the letters, addressed to the community of priests, deal with many topics related to priestly life. Their common feature is an anthropological perspective. In the analyzed writings, Pope John Paul II describes issues related to the ministerial priesthood, such as the role of the priest in the life of the Church community, or priestly identity and spirituality with an emphasis on Christ. The author has conducted research and articulated the characteristic features that emerge during the discourse on the priesthood of Jesus Christ.